Measures of river channel efficiency through cross-sectional form - Das, Balai Chandra; Islam, Aznarul; Das, Uddalak (Bulletin of Geography. Physical Geography Series, 2025)
The efficiency of an open river channel refers to how effectively the channel conveys water with minimal energy loss due to friction with the perimeter. Cross-sectional form, roughness characteristics and slope play pivotal roles in governing a channel’s efficiency. Previous studies commonly used hydraulic radius (Rh) and width/depth ratio (ζ=w/d̄) to assess channel efficiency. Rh lacks a dimensionless representation for comparing rivers of different sizes, while the ζ value has no specific scale (e.g., 0 to 1) to fix a channel’s efficiency level. This research specifically investigates the influence of channel cross-sectional form on efficiency, assuming a given slope and roughness, and presents novel tools for measuring channel efficiency based solely on cross-sectional form. It is widely acknowledged that a semi-circular cross-section represents the most efficient channel form due to its minimal wetted perimeter. However, little attention has been given to comparing an open channel with an ideal semi-circular form and establishing a fixed efficiency parameter. Hence, three handy tools are proposed to measure the efficiency of open-channel cross-sectional forms. The first tool (E1) compares the cross-sectional area of the observed channel with the area of a semicircle having an equivalent perimeter; we define channel efficiency, E1, as the “ratio of the cross sectional area (A) of the channel, to the area of a theoretical semicircle (Ac) having the same wetted perimeter P”. The second tool (E2) compares the wetted perimeter of the channel with the perimeter of a semicircle of the same area as the observed cross-section. Finally, the third tool (E3) assesses the width/depth ratio of the observed channel by comparing it to the width/depth ratio of a semicircle of the same area. The effectiveness of these tools was validated using a computed dataset of size 1080 and a field-based dataset comprising 45 cross-sections obtained from the Jalangi River in India. The major highlights of the methods are as follows. • Three new indices of channel efficiency are proposed using the cross-sectional form. • The proposed methods are unit-free, with known scale limits for comparison. • The proposed indices are validated using field data from a tropical river.